IMPLEMETASI ASAS OPORTUNITAS DI INDONESIA - Setiawan, Dwi Nugroho (2024)
This study aims to find out and analyze the history of the origins of the opportunity principle in Indonesia and also the development of the opportunity principle in Indonesia and also the problems contained in Article 35 letter c of Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia, and how to analyze become a consideration in the public interest as the basis for the application of the principle of opportunity by the Attorney General. The research method used in this study uses a qualitative approach to literature study. The data obtained from this research is secondary data, and analyzed qualitatively. The results of this study indicate that the authority to set aside cases in the public interest applies to anyone, while the implementation of dismissal of cases in the public interest can be divided into 2, in which the interests of the nation and state and also the interests of the wider community, if the interests of the nation and state must consist of unity and national and state unity, peace and general welfare, stability of the wheels of government. Meanwhile, for the benefit of the wider community, it must consist of preventing violations of rights, preventing moral decline, social protection and general welfare.